Kv1.3 Channel as a Key Therapeutic Target for Neuroinflammatory Diseases: State of the Art and Beyond - Wang, Xiaoli; Li, Guoyi; Guo, Jingkang; Zhang, Zhiping; Zhang, Shuzhang; Zhu, Yudan; Cheng, Jiwei; Yu, Lu; Ji, Yonghua; Tao, Jie (Frontiers in Neuroscience, 2020)
It remains a challenge for the effective treatment of neuroinflammatory disease, including multiple sclerosis (MS), stroke, epilepsy, and Alzheimer’s and Parkinson’s disease. The voltage-gated potassium Kv1.3 channel is of interest, which is considered as a novel therapeutic target for treating neuroinflammatory disorders due to its crucial role in subsets of T lymphocytes as well as microglial cells. Toxic animals, such as sea anemones, scorpions, spiders, snakes, and cone snails, can produce a variety of toxins that act on the Kv1.3 channel. The Stichodactyla helianthus K+ channel blocking toxin (ShK) from the sea anemone S. helianthus is proved as a classical blocker of Kv1.3. One of the synthetic analogs ShK-186, being developed as a therapeutic for autoimmune diseases, has successfully completed first-in-man Phase 1 trials. In addition to addressing the recent progress on the studies underlying the pharmacological characterizations of ShK on MS, the review will also explore the possibility for clinical treatment of ShK-like Kv1.3 blocking polypeptides on other neuroinflammatory diseases.